Enhancing Maternal Self-Efficacy Through Family-Centered Maternity Care: A Literature Review - Ika Novita Sari (Sahabat Publikasi Kuu, 2024)
Maternal self-efficacy (MSE) is a critical factor in women's adaptation to motherhood and the well-being of both mother and infant. Family-Centered Maternity Care (FCMC) is an approach that emphasizes family involvement in the pregnancy and childbirth process. This literature review examines the relationship between FCMC and MSE through a comprehensive analysis of theoretical and empirical literature. The findings suggest that FCMC has the potential to enhance MSE through increased social support, observational learning, and mastery experiences. Implications for midwifery practice and future research directions are discussed